2017
DOI: 10.1039/c7lc00295e
|View full text |Cite
|
Sign up to set email alerts
|

Liter-scale production of uniform gas bubbles via parallelization of flow-focusing generators

Abstract: Microscale gas bubbles have demonstrated enormous utility as versatile templates for the synthesis of functional materials in medicine, ultra-lightweight materials and acoustic metamaterials. In many of these applications, high uniformity of the size of the gas bubbles is critical to achieve the desired properties and functionality. While microfluidics have been used with success to create gas bubbles that have a uniformity not achievable using conventional methods, the inherently low volumetric flow rate of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 38 publications
(28 reference statements)
0
42
0
Order By: Relevance
“…In previous work, architectures have been developed that make it possible to operate many microfluidic droplet generators in parallel 11 22 . While great progress has been made in these approaches, current chips with parallelized devices are limited to production rates ϕ max ⪍ 1 L h −1 , have droplet homogeneities set by three-dimensional (3D) soft-lithography fabrication 15 , are limited to low temperature and pressure operation, can only be used with the solvents compatible with the device’s polymer construction, or are unable to be adapted to produce higher-order emulsions and particles that require multi-step processing 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, architectures have been developed that make it possible to operate many microfluidic droplet generators in parallel 11 22 . While great progress has been made in these approaches, current chips with parallelized devices are limited to production rates ϕ max ⪍ 1 L h −1 , have droplet homogeneities set by three-dimensional (3D) soft-lithography fabrication 15 , are limited to low temperature and pressure operation, can only be used with the solvents compatible with the device’s polymer construction, or are unable to be adapted to produce higher-order emulsions and particles that require multi-step processing 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that the fluid flow rates are uniform throughout the device, we use the previously reported ladder geometry, which has proven to be a robust approach to enable large-scale production of simple emulsions and bubbles. 19,21 Briefly, gas, water and oil phases are introduced into the device through respective inlets and divided into 8 sets of distribution channels that run horizontally as illustrated in Figure 1 width, height and length of the channel and the viscosity of the fluid). 40 This criteria states that the resistance of distribution channel (R d ) between two adjacent FFGs should be significantly smaller than the resistance of a single FFG (R f ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study on the parallelization of simple gas bubble production has shown that it is helpful to use a device with a smaller number of parallel FFGs to study the effect of fluid flow rates on the size and uniformity of produced emulsions or bubbles to identify ideal flow rates that will lead to stable emulsion formation, and that these flow conditions can be used successfully in devices with greater numbers of FFGs. 21 In this work, we use the same strategy to find optimal flow conditions. Specifically, we use a device with 8 parallel FFGs to study how the changes in the flow rates influence the formation of G/W/O compound bubbles and their uniformity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations